Characteristics Analysis of Leakage Current in an Array of InSb Photodetector: The Effect of Compressive and Tensile Stresses. Issue 3 (5th January 2023) - Heidarzadeh, Hamid
Abstract : Herein, the effect of tensile and compressive stress on the performance of a 3 × 3 InSb array as an infrared photodetector is investigated. At first, the effect of mesh sizes on simulated results is evaluated and the results are validated with a good agreement. It is shown that the main effect of stress is related to the Γ (bandgap) point of the band structure. This shift causes the densities of intrinsic and minority carriers to decrease in the case of tensile stress and increase in the case of compressive stress. Using a 3D simulation, it is investigated that tensile stress reduces the dark current while compressive stress induces that. However, it is an interesting result that an increment in applied compressive stress interrupts the InSb photodetector performances and vice versa tensile stress helps the photocurrent to have a lower dark current. So, these results can be used to manage the dark current in the field of the photodetector. Finally, the crosstalk of the simulated structure as one of its main characteristics is calculated. Abstract : This research work presents the effect of tensile and compressive stress on the performances of a 3 × 3 InSb infrared photodetector array. The obtained results show that leakage current strongly depends on the types of applying stress (tensile and compressive stress). Tensile stress reduces the leakage current while compressive stress induces that.